2007
DOI: 10.1063/1.2750652
|View full text |Cite
|
Sign up to set email alerts
|

A long plasma column in a flexible tube at atmospheric pressure

Abstract: A radio-frequency nonequilibrium atmospheric pressure plasma operating with argon and oxygen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…As the plasma plume cross section is more or less 1.3 mm, the tube with an inner diameter of 1.02 mm fits best of all tubes to this size. This observation is in close agreement with previously published results in which an excellent plasma propagation has also been observed when the size of the plasma source and flexible tube is almost the same. The reason of the plasma penetration has been associated with accumulation of the surface charge on the internal walls of the tubes resulting in an enhancement of the electric field inside the tubes …”
Section: Resultssupporting
confidence: 93%
“…As the plasma plume cross section is more or less 1.3 mm, the tube with an inner diameter of 1.02 mm fits best of all tubes to this size. This observation is in close agreement with previously published results in which an excellent plasma propagation has also been observed when the size of the plasma source and flexible tube is almost the same. The reason of the plasma penetration has been associated with accumulation of the surface charge on the internal walls of the tubes resulting in an enhancement of the electric field inside the tubes …”
Section: Resultssupporting
confidence: 93%
“…As a matter of fact, it was reported that the atmospheric pressure argon plasma generated at 20 kHz with a typical injection needle placed in a Teflon tube was as long as 1000 mm. 9 The current and voltage were measured using a current probe ͑Pearson 4100͒ and a voltage probe ͑Tektronix P6015A͒, and wavelength-unresolved visible emission from the plasma was measured using a photomultiplier tube ͑Hamamatsu R928-10͒. Figure 2͑a͒ depicts waveforms of input voltage, total current, and optical emission signal of the LF plasma.…”
mentioning
confidence: 99%
“…Many plasma jet devices that produce a cold atmospheric-pressure plasma plume have been investigated for their use with thermally sensitive materials and medical applications [4][5][6][7][8][9][10][11][12]. For example, Nie et al [9] presented a simple cold plasma jet with a length of several centimeters that utilized floating electrodes in a quartz tube under high voltage.…”
Section: Introductionmentioning
confidence: 98%